Determinants of Choosing Sources of Financing for Municipal Projects - Petrov, Dancho (Vallis Aurea, 2023)
The paper discusses various alternatives for financing socially significant projects of municipalities. Having in mind the opportunities and limitations of municipal budgets and the example of the municipality of Burgas, the paper analyzes positive and negative sides of financing with own resources, bank loans, bond issues, pooling and revolving schemes. The focus of the research are the factors that influence the choice of a financing alternative –costs of funding, level of financial infrastructure, regulative conditions, debt risk, level of decentralization and opportunities for generating revenues. By use of selected diagnostic indicators there are outlined the challenges to successful realization of socially significant municipal projects.